Parisian Labour During the French Revolution - Sibalis, Michael (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1986)
AbstractWorkers in revolutionary Paris did not show the class consciousness nor, with certain exceptions, the organizational skills of the workers' movement after 1830. Nevertheless, an analysis of eighty-five recorded labour disputes proves labour protest to have been a significant form of protest in the capital between 1789 and 1799. Sans-culotte unity has been exaggerated, and wage-earners articulated demands (principally for higher wages) that set them apart from the master-craftsmen and shopkeepers who directed the sans-culotte movement. The response of the authorities to labour unrest was often hesitant and contradictory, and the repressive Le Chapelier law of 1791 was in fact rarely invoked.